Relation of Moderate Physical Activity to Blood Markers of Oxidative Stress and Antioxidant Defense in the Elderly. (11th February 2019) - Kozakiewicz, Mariusz; Rowiński, Rafał; Kornatowski, Maciej; Dąbrowski, Andrzej; Kędziora-Kornatowska, Kornelia; Strachecka, Aneta
Abstract : The aim of the present study was to establish whether markers of oxidative stress and the enzymatic defense system of the blood are related to moderate physical activity in younger old and the oldest old men. They were divided into four groups according to the age and level of physical activity (groups YN and YA—inactive and active younger old men aged 65-74 years, groups ON and OA—inactive and active oldest old men aged 90-99 years). Venous blood was collected from the subjects in the morning before breakfast. MDA concentration and antioxidant enzyme activities (SOD, CAT, GPx, and GR) in erythrocyte hemolysates were assayed. The concentration of isoprostanes (8-iso-PGF2 α ) and carbonyl groups in protein (CP) was measured in plasma and serum. All assayed antioxidant enzyme activities and the SOD/GPx ratios were significantly higher in the active younger old males than in all the inactive ones. In the group of oldest old active participants, only the GPx activity was significantly higher compared to the inactive oldest old males. The activity of CAT and GPx in the younger old inactive men was significantly lower than that in the oldest old inactive subjects. However, SOD, CAT, and GR activities and SOD/GPx ratio were significantly higher in the younger old active men compared to the oldest old active participants. The concentrations of isoprostanes, protein carbonyls, and MDA were significantly lower in both active and inactive younger old males than in the respective groups of the oldest old men and in both groups of active men, independently of age, compared to the respective inactive subjects. The present study confirmed that oxidative stress is related to age. Physical activity caused a decrease of oxidative stress markers independently of age and resulted in an increase of GPx activity in both younger old and the oldest old active groups.